Existence of a Solution of a Certain Volterra -Fredholm Integro Differential Equations - Akram H. Mahmood; Lamyaa H. Sadoon (College of Education for Pure Sciences, 2012)
Abstract In this paper, e investigate the existence of global solution for nonlinear mixed Volterra-Fredholm integro differential equation with nonlocal condition in Banach space. Our results depend on Leray -Schauder alternative theorem.